Analisis Terjemahan Tuturan Direktif pada Subtitle Drama Jimi Ni Sugoi! Kouetsu Garu: Kouno Etsuko - Harywardani, Ayu Anova; Antartika, I Kadek; Yeni, Yeni (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025), 2025)
This research aims to describe the translation of directive speech in the Indonesian subtitles of the drama Jimi ni Sugoi! Kouetsu Garu Kouno Etsuko. This research is a qualitative descriptive using the listening and note-taking method. The theories used are Austin's directive speech theory in Ibrahim (1993) and the translation technique theory of Molina & Albir (2002). This research data was analyzed using element sorting and glossing techniques, and the translational equivalent method. Based on the research results, there are 6 types of directive speech were found, namely requests, interrogations/questions, orders, permission, prohibitions and suggestions. Then translated using 9 types of translated speech, namely amplification, discursive creation, general equivalence, generalization, linguistic amplification, literal, modulation, particularization and reduction. Linguistic amplification dominates directive speech translation techniques.